Unravelling Surface Seawater DMS Concentration and Sea‐To‐Air Flux Changes After Sea Ice Retreat in the Western Arctic Ocean. Issue 6 (24th June 2021) - Zhang, Miming; Marandino, Christa. A.; Yan, Jinpei; Wu, Yanfang; Park, Keyhong; Sun, Heng; Gao, Zhongyong; Xu, Suqing
Abstract: The receding of the seasonal ice cover in the Arctic due to climate change has been predicted by models to increase climate‐active biogenic trace gas emissions, specifically those of dimethylsulfide (DMS). However, insufficient DMS measurements are currently available to either support or refute this hypothesis and to fully understand the various responses of oceanic DMS in a rapidly changing Arctic Ocean environment. Here, we present high‐resolution surface water DMS data collected in the summer of 2014 in combination with a suite of ancillary variables including sea ice cover, salinity, and nutrients. We show that surface seawater DMS concentrations, generally below 0.5 nmol L −1, remained unchanged in the Canada Basin after sea ice retreat probably due to insufficient nutrients supply to the upper mixed layer and resulting low primary production. Moreover, in the Chukchi shelf region, DMS concentrations decreased following a phytoplankton bloom due to the rapid depletion and slow resupply of nutrients. Although the DMS sea‐to‐air fluxes were not high from a global perspective, they increased by a factor of 4‐fold after sea ice retreat in the Arctic Ocean high latitudes. This increase in DMS flux was mainly driven by increased wind speed. This work provides unique observations and insights on how surface seawater DMS and flux to the atmosphere may change in the future Arctic Ocean. Key Points: Surface seawater dimethylsulfide (DMS) concentrations remain unchanged after sea ice retreat in the western Canada Basin Increased wind speed is a critical factor driving the enhancement of dimethylsulfide (DMS) flux after sea ice retreat at high latitudes in the Arctic Ocean Nutrient supply is hypothesized to significantly impact dimethylsulfide (DMS) distribution in the western Arctic Ocean